Analysis of The Correlation Between Mechanical Engineering Research and COVID-19 Situation: Bibliometric Study - Ramadhan, Doni Fajar; Saputra, Nisa Aulia; Sumirat, Uum (Fakultas Teknik Universitas Negeri Malang, 2022)
The rapid spread of the coronavirus has a bad impact on many things, including education, government, the economy. This study was conducted to investigate the development of mechanical engineering research by mapping bibliometrics using the R programming language and VOSviewer. Bibliometric classifications indicate the types of publications, keywords trend, and authors of scientific papers. In this study, data collection was performed from the SCOPUS and dimensions.ai website. This website provides a dataset of scientific papers published in international peer-reviewed journals. The keyword that we used to collected the metadata